Inhibition of Kelch-like epichlorohydrin-related protein 1 promotes the progression and drug resistance of lung adenocarcinoma - Gao,Hong; Tang,Peipei; Ni,Kejie; Zhu,Lun; Chen,Song; Zheng,Yulong; Wan,Yufeng (PeerJ, 2021)
Background Lung cancer is a common malignant carcinoma of respiratory system with high morbidity and mortality. Kelch-like epichlorohydrin-related protein 1 (Keap1), a member of the BTB-Kelch protein family, has been reported as an important molecule in several cancers. However, its potential role in tumor is still controversial. Here we aim to clarify the effect of Keap1 on the biological characteristics and chemotherapy resistance in lung adenocarcinoma (LUAD). Methods Immunohistochemistry was conducted to compare Keap1 expression in lung adenocarcinoma tissues and matched non-cancerous tissues, and the correlation between Keap1 expression and clinicopathological features was analyzed. Subsequently, the stable A549 and H1299 cell lines with Keap1 knockdown or overexpression were constructed using lentivirus. The roles of Keap1 on the cell proliferation, migration, invasion and drug resistance were investigated by colony formation assay, cell proliferation assay, wound scratch test, transwell invasion assay and drug sensitivity assay, respectively. Results Keap1 was lowly expressed in tumor tissues compared to matched non-cancerous tissues, and its expression was correlated with TNM stage and lymph node metastasis. Early stage (I) tumors without lymph node metastasis had higher levels of Keap1 expression compared with late-stage tumors (II, III) with the presence of lymphatic metastasis. Colony formation assays showed that Keap1 knockdown promoted the proliferation of A549 and H1299 cells, and the cell growth curves further confirmed this feature. In contrast, wound scratch and transwell invasion experiments showed that Keap1 overexpression inhibited cell migration and invasive malignancy. The IC50 for cisplatin and paclitaxel were significantly increased by Keap1 knockdown in A549 and H1299 cell lines. Conclusion Keap1 knockdown promotes tumor cell growth, proliferation, invasion, metastasis and chemotherapy resistance in LUAD. It may be a potential tumor marker to guide the staging and treatment of lung cancer.
Keywords: Keap1; LUAD; Progression; Drug resistance